Pengaruh Wacana Kenaikan Tarif Candi Borobudur Terhadap Minat Wisatawan dan Jumlah Pemesanan Jasa Travel - Joko Triyono; Dwi Yoso Nugroho (Universitas Pendidikan Ganesha, 2022)
This study aims to determine the effect of the discourse on increasing entrance tickets to Borobudur Temple on the interest of visiting tourists and the number of bookings for travel services. This study uses a questionnaire as a data collection material, which is then analyzed by multiple linear regression method using SPSS 26 software. The independent variable used is the discourse on increasing entrance tickets to the Borobudur Temple tourist area, as well as interest in visiting tourists and booking travel services as the dependent variable. The results of this study indicate that the discourse of increasing entrance tickets to Borobudur Temple has a negative influence on tourist interest in visiting and the number of bookings for travel services. it is proven that there is a positive and significant influence on the discourse on the increase in ticket prices on the interest of tourists visiting Borobudur Temple. In addition, it is proven that there is a positive and significant influence on the variable about the increase in ticket prices on booking travel services.